ANALISIS USABILITY SISTEM PAKAR MASKER ORGANIK MENURUT JENIS KULIT MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Inike fatanah, Inike fatanah; Amna, Amna; dewi, Ratna (Jurnal Teknik Informatika dan Elektro, 2023)
Masks are one of the most commonly used facial skin treatments to keep the skin looking fresh and clean. This mask can be used by various groups ranging from teenagers to the elderly. One way to treat facial skin is very easy and does not take a long time to use. Masks can maintain, treat facial skin and increase skin regeneration and treat facial skin. Along with the development of the cosmetic industry, many cosmetic products have emerged with various advantages, especially in terms of the composition of the product. One of the most popular cosmetic products is face masks. The fact that the development of the cosmetic industry makes it difficult for consumers to choose a mask product that suits their skin condition, especially those who do not understand face masks. When consumers choose the wrong face mask, more severe skin problems will arise. So masks based on the selection of skin conditions are important.